Energy-based economic development: Mapping the developing country context - Sanya Carley; Sameeksha Desai; Morgan Bazilian (Fondazione Eni Enrico Mattei (FEEM), 2012)
Energy-based economic development (EBED) can provide economic, social and environmental benefits related to national economic development and sustainable growth activities. As both policy and research interests in responsible mechanisms for economic development grow, EBED benefits are becoming increasingly attractive to planners in both developed and developing countries. The incentives, trade-offs, and payoffs for developing countries, however, are not well documented. To help address that gap, this paper identifies the general scope and role of EBED in a developing economy context, and outlines opportunities and challenges for decision-makers.
Keywords: O10; O13; O21; Q48; 330; Economic Development; Energy; Developing Countries; Sustainable Development